The Effect of Health Education on the Level of Knowledge About Anemia in Adolescent - Silvi Ratna Fiani; Firdawsyi Nuzula; Haswita Haswita (Humanistic Network for Science and Technology (HNST), 2021)
Anemia is one of the most common nutritional problems, especially in adolescents which is usually caused by iron deficiency and the increasing need for iron at that time. The provision of health education to young women aims to overcame the high problem of anemia and is one solution to increase knowledge about anemia. This study aims to identify the effect of health education on the level of knowledge about anemia in adolescent girls at SMK Negeri 17 August 1945 Genteng. This study used control group pre-test and post-test design. The population of this study were 225 students with a sample of 100 students who were selected using purposive sampling technique. The instrument used was questionnaire about knowledge of anemia and health education with leaflets and video power point media. The analysis technique used was the paired samples t-test. The results of the analysis showed p-value of <0.001, it means that there is an effect of health education on the level of knowledge about anemia in adolescent girls. It is hoped that after health education about anemia in adolescent girls can prevent anemia, especially during menstruation.Keywords: anemia; health education; knowledge